Chemical Stability of Ketoconazole 2% in Polyethylene Glycol Ear Drops - Chailertwanich, Ornpapa; Noppawinyoowong, Chedsada (Srinagarind Medical Journal, 2015)
Background and Objectives : According to the Thai National Formulary 2013, clotrimazole ear drops was a single topical antifungal agent indicated for the treatment of otomycosis and available commercially. Ketoconazole ear drops was developed as alternative medication for patients who did not response to clotrimazole. To assure the quality of the developed product, the chemical stability of 2% ketoconazole ear drops was studied for 180-days period. Methods : The experiment on chemical stability of 2% ketoconazole ear drops was conducted at Srinagarind hospital. Ketoconazole solution was prepared by dissolving ketoconazole powder in polyethylene glycol 400 and stored at room temperature. The samples were analyzed for the concentrations of ketoconazole on days 0, 30, 60, 90, 120, 150 and 180 by using HPLC. Results : The mean percentages of labeled amount were 102.43, 102.70, 100.70, 97.50, 90.10, 85.80 and 84.30 on days 0, 30, 60, 90, 120, 150 and 180, respectively. The mean percentages of the initial concentration remaining of ketoconazole were 100.00, 100.26, 98.31, 95.18, 88.02, 83.79 and 82.26 on days 0, 30, 60, 90, 120, 150 and 180, respectively. The concentrations of ketoconazole remained less than 90 percent on days 120, 150 and 180. Conclusions : The result of the study indicated that 2% ketoconazole ear drops, consisting of ketoconazole and polyethylene glycol 400 were stable within 90 days when stored at room temperature.